Patent Do's and D'oh!. - Frank, S.J (IEEE spectrum)
The process of getting a US patent goes something like this: you work with your patent lawyer or agent to prepare an application that describes your invention in exhaustive detail; the Patent Office rejects all of your claims in curt, dismissive terms; your counsel says not to panic and, in most cases, persuades the patent examiner to allow at least some claims; and, finally, two or more years after you first filed, agony gives way to ecstasy and the beribboned patent deed issues forth. But legal traps along the way may deprive the unwary of some or even all patent riots. Worse, you may not learn of a mistake until years later, after the patent has issued, when some alert lawyer asks a few innocent-sounding questions about a conference paper you gave and, shortly after, asks the court to invalidate your patent. The author describes how the most common mistakes fall into three categories: those that threaten US rights, those affecting foreign rights, and the effects of patent filings on trade secrets.